2004
DOI: 10.1249/01.mss.0000126777.50188.73
|View full text |Cite
|
Sign up to set email alerts
|

Motion Sensor Accuracy under Controlled and Free-Living Conditions

Abstract: Different brands of motion sensors detect steps differently; therefore, caution must be used when comparing step counts between studies that have employed different brands of motion sensors. Taking into consideration the results of both studies and the initial walking test used for instrument screening purposes, it appears that, of the three pedometers tested, the YAM pedometer is most consistently accurate under both controlled and free-living conditions. Future research must consider presenting motion sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
183
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(198 citation statements)
references
References 13 publications
11
183
1
3
Order By: Relevance
“…The SW pedometer range has been shown to accurately detect steps in controlled laboratory (Le Masurier and Tudor-Locke 2003;Swartz et al 2003;Melanson et al 2004) and freeliving conditions (Le Masurier et al 2004;Schneider et al 2004) and has consequently been employed in numerous free-living activity studies (Chan et al 2004;Tudor-Locke et al 2004b;Hornbuckle et al 2005). The pedometer accurately assesses walking activity of all BMI classifications (Swartz et al 2003).…”
Section: Physical Activity Assessmentmentioning
confidence: 99%
“…The SW pedometer range has been shown to accurately detect steps in controlled laboratory (Le Masurier and Tudor-Locke 2003;Swartz et al 2003;Melanson et al 2004) and freeliving conditions (Le Masurier et al 2004;Schneider et al 2004) and has consequently been employed in numerous free-living activity studies (Chan et al 2004;Tudor-Locke et al 2004b;Hornbuckle et al 2005). The pedometer accurately assesses walking activity of all BMI classifications (Swartz et al 2003).…”
Section: Physical Activity Assessmentmentioning
confidence: 99%
“…19 Only one study in Japan has used a form of objective measurement (an accelerometer) to assess physical activity, and this study reported a significant negative relationship between depressive mood and physical activity. 12 Pedometer is another tool for measurement of physical activity commonly used in other studies; however, it is not sensitive to slow activity or shuffling gaits 20,21 and it also motivates physical activity, 22,23 so it may either under or overestimate physical activity in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…A cover over the control buttons prevents the unit from being inadvertently reset or stopped. The DW is considered accurate 5,6,9,21,32 and durable, 24 and has been used for large-scale surveys 4,36 and in experimental trials. 16,27 The DW is a popular brand of pedometer and has been used in public health initiatives similar in concept to the Kellogg's and Discovery initiatives.…”
Section: Pedometersmentioning
confidence: 99%
“…12 Although the marketing initiatives of Kellogg's South Africa and Discovery Health are laudable, the accuracy and longevity of the pedometers are not reported. Calibration studies have found that the accuracy 5,9,21,22,25,32 and longevity 24 of pedometers vary considerably between brands. Recent validation trials of promotional pedometers in Europe 10 and North America 14,37 have found poor instrument accuracy and consistency.…”
Section: Introductionmentioning
confidence: 99%